(untitled) (Advances in Applied Biological Research, 2025)
New anti-diabetic compounds can be obtained from Indian herbal remedies, which are employed in the ancient Ayurvedic approach to manage hyperglycemia. A common medicinal plant, H. marifolium is a significant reservoir of compounds with potent antioxidant action. The main objective of the study was to find out the anti-inflammatory activities, antioxidant and antidiabetic effect of selected medicinal plant. Conventional parameters such as DPPH, ABTS, hydroxyl, superoxide radical, nitric oxide, and hydrogenperoxide assay were performed. The chromogenic iodine technique was used to quantitatively determine the activity of extracts in relation to amylase inactivation. At 250µg, the leaves extraction had a much stronger scavenge action (>75%) than the stem extraction (<75%). Both samples exhibited dose-related enhancements in antioxidant activity. When compared to its standard a low scavenging activity at 50µg concentration and comparable scavenging activity at 300µg was recorded among extract. One of the well-established roots of inflammation, protein denaturation, was successfully controlled by the use of the extract. Both extracts were discovered to have a non steroidal anti-inflammatory activity. Additionally antidiabetic study shows that the standard inhibitor, acarbose, has an least IC50 value of 122.37 μgml-1, following that the leaf and stem extracts (187.30 μg ml-1 and 209.26 μg ml-1, respectively). The data confirms that the primary compounds found in stem and leaf extracts may promote the effectiveness of antidiabetic, anti-inflammatory, and antioxidant nature of the plant.